2011
DOI: 10.1063/1.3585138
|View full text |Cite
|
Sign up to set email alerts
|

Molecular monolayers for conformal, nanoscale doping of InP nanopillar photovoltaics

Abstract: Semiconductor nanopillar arrays with radially doped junctions have been widely proposed as an attractive device architecture for cost effective and high efficiency solar cells. A challenge in the fabrication of three-dimensional nanopillar devices is the need for highly abrupt and conformal junctions along the radial axes. Here, a sulfur monolayer doping scheme is implemented to achieve conformal ultrashallow junctions with sub-10 nm depths and a high electrically active dopant concentration of 1019–1020 cm−3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…As opposed to the top-down method, bottom-up fabrication of nanostructures is an enticing approach to fabricate nanostructures without using costly processes such as lithography and dry-etching. [ 5,17,22,32,51,63,64,[74][75][76][77] As an example, Fan et al reported ordered arrays of Germanium (Ge) dual-diameter Nanopillars (DNPLs) with different diameters at the tip and base fabricated inside self-organized anodic aluminum oxide (AAO) templates. Such DNPLs presented an impressive absorption of 99% of the incident light over a wavelength ranging from 300 to 900 nm with a thickness of only 2 µm.…”
Section: Brief Review Of Light Harvesting With Nanostructuresmentioning
confidence: 99%
“…As opposed to the top-down method, bottom-up fabrication of nanostructures is an enticing approach to fabricate nanostructures without using costly processes such as lithography and dry-etching. [ 5,17,22,32,51,63,64,[74][75][76][77] As an example, Fan et al reported ordered arrays of Germanium (Ge) dual-diameter Nanopillars (DNPLs) with different diameters at the tip and base fabricated inside self-organized anodic aluminum oxide (AAO) templates. Such DNPLs presented an impressive absorption of 99% of the incident light over a wavelength ranging from 300 to 900 nm with a thickness of only 2 µm.…”
Section: Brief Review Of Light Harvesting With Nanostructuresmentioning
confidence: 99%
“…[8,95] However, the prevalence of carrier recombination in nanostructured solar cells results in electrical losses that counteract the optical gains, therefore it is difficult for such devices to exceed the J SC and efficiency of conventional solar cells made using standard AR coatings. [96][97][98][99] Even the world record Si-nanostructured solar cell, made with Al 2 O 3 as an AR and passivation layer, featured a J SC and energy conversion efficiency of only 0.2 mA cm −2 and 0.1% higher than a solar cell made with traditional micropyramidal structures. [9] The fundamental problem is the increased surface recombination of nanostructures, which leads to a corresponding decrease in the Voc of nanostructured solar cells.…”
Section: Optical/electrical Tradeoffs Of Nanostructured Solar Cellsmentioning
confidence: 99%
“…However, its solar efficiency is still lower than that of planar InP homojunction solar cells, which use traditional AR coatings, indicating just how great an impact nanostructures can have on electrical losses and thus the overall device performance. [99,142] Engineering new solar device architectures provides a promising way to exclude the severe surface and Auger recombination effects that compromise nanostructured materials. For example, IBC design has been used to improve efficiency for thick Si solar cells for some time.…”
Section: Device Architecture Engineeringmentioning
confidence: 99%
“…Monolayer doping is used in an increasing number of applications that require the controlled doping of nanostructures and for achieving ultrashallow surface doping of semiconductors. [ 20–25 ] Advances in monolayer doping provide significant progress in obtaining improved properties, including higher doping densities and various aspects of the monolayer doping method. [ 18,26 ] Monolayer doping involves the thermal fragmentation of the monolayer followed by dopant activation and diffusion.…”
Section: Introductionmentioning
confidence: 99%